Occupational exposure to Cr(VI) in Finland in 1980–2016 and related lung cancer risk assessment - Mahiout, Selma (2022)
Occupational exposure to hexavalent chromium [Cr(VI)], a known lung carcinogen, remains a relevant concern. When performing exposure assessment for risk assessment, biomonitoring is an important tool, reflecting actual internal exposure of workers. Here, we present total urinary chromium (U-Cr) biomonitoring data from several occupational sectors, spanning 1980-2016 (n > 42,000). Based on this data, we estimated lifelong (40-year) occupational lung cancer risks in the Cr-plating and welding sectors. We used published regression formulas to relate internal (U-Cr) and external Cr(VI) inhalation exposures, allowing risk assessment based on a published lung cancer dose response. Generally, measured U-Cr levels decreased considerably over the study period. The highest U-Cr P95 levels (representing realistic worst-case) were measured in 1980-1989 in casters, maintenance workers, and welders (40-45 μg/L). By 2010-2016, the U-Cr P95 had decreased to ≤9.5 μg/L in all studied sectors. Lifelong external Cr(VI) exposure estimation for 1980-2019 was 0.16-0.32 mg/m3 x year for platers and 1.03 mg/m3 x year for welders. Worst-case lifelong lung cancer relative risk (RR) estimates were 1.28-1.56 for platers and 2.80 for welders; attributable risks (AR) were 22-36% for platers and 64% for welders. Uncertainties that may have impacted the risk assessment are discussed.